Behaviour of contrasting cassava genotypes in different planting systems - Bueno, Alvaro (Pesquisa Agropecuaria Brasileira, 2014)
Ten cassava (Manihot esculenta Crantz) cultivars, five high branching and five low branching, were evaluated under similar painting densities in single and double rows during two crop years in Cruz das Almas-BA. The experimental design was a split-plot with planting systems assigned to the main plots and cultivars randomized in the sub plots. The single row system was more efficient than double row since it promoted higher root yield due, mainly, to a larger number of roots per plant formed in the single rows. Upper part yield was similar in both systems. High branching cultivars showed, in both years, higher average root yield than did the low branching group, however upper part yield was similar for both groups. Cultivars BGM 001 (Aipim Bravo) and BGM 340 (CM 305/5) showed, respectively, the highest and the lowest root yield, number of roots par plant and average root weight. The most vigorous upper part was developed by cultivar BGM 361 (Arrebenta Burro). Interactions involving cultivars and planting systems were not significant for all variables, suggesting that planting systems did not influence differently the behaviour of all cultivars, irrespective of their branching habits.